Moringa Jamu (Recipe Formulation, Hedonic Test And Nutrition) - Ni Putu Eka Trisdayanti; I Made Purwa Dana Atmaja (Universitas Pendidikan Indonesia, 2022)
Consumption of natural immune-boosting foods/drinks without preservatives such as jamu is a very good thing. Jamu processing is carried out from generation to generation based on ancestral recipes, and uses existing natural ingredients. However, over time the existence of jamu began to decline due to the circulation of modern medicines. In fact, jamu is not just a traditional medicine, but one of the efforts to maintain the biodiversity of the Indonesian nation. Therefore, it is important to bring jamu to the family menu in order to maintain the existence of jamu and its development. In addition, during the pandemic, people requires strong stamina, hence the researchers are interested in conducting research on jamu, especially moringa jamu, because moringa jamu is not yet common in the community. The author conducted an experiment on processing moringa jamu to get a recipe formulation, hedonic test (preference test) on 100 panelists with 3 hedonic scales namely very like, like, and dislike, as well as nutrition tests (carbohydrates, protein, fat, calories, vitamin C, and antioxidants). The results of this study are the formulation of the moringa jamu recipe, namely 100 g of moringa leaves, 1 liter of water, 20 g of tamarind, 100 g of brown sugar, 5 g of salt, lime (optional). The method of processing moringa jamu is by heating 500 ml of water, tamarind, brown sugar, and salt, then set aside, blend the moringa leaves, add 500 ml of water, and then heat it, mix them and then filter. The results of the hedonic test of moringa jamu, namely 61% of panelists said they really liked it, 39% of panelists said they liked it, and 0% dislikes it. The nutritional content of moringa jamu is 8.43% bw of carbohydrates, 1.41%bw of protein, 0.05% bw of fat 39.79 kcal calories.